2019
DOI: 10.1177/1534734619832123
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Outcomes of Split-Thickness Skin Graft on Diabetic Leg and Foot Ulcers

Abstract: Diabetic lower limb ulcers are a serious complication to diabetes that could lead to amputation and death. Split-thickness skin graft (STSG) has been proposed by some authors to treat noninfected diabetic wounds, mainly those found in the leg and on the dorsum of the foot. No quantitative evidence synthesis over this technique has been reported in the literature. The study is a meta-analysis on the effectiveness of STSG in treating diabetic leg and foot ulcers. Electronic databases were searched from inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Certainly, the choice to follow the standard protocol and to perform a skin graft after the application of a DES is the usual choice 24,25 ; however, our experience also supports the use of this type of DES and under which conditions a skin graft is not be performed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Certainly, the choice to follow the standard protocol and to perform a skin graft after the application of a DES is the usual choice 24,25 ; however, our experience also supports the use of this type of DES and under which conditions a skin graft is not be performed.…”
Section: Discussionmentioning
confidence: 57%
“…DFUs can be sources of unstable scars and increase the risk of recurrence. 25 Nonetheless, the quality of the new skin, without scars, observed in our patients could significantly reduce the risk of relapse, mainly in the loading areas.…”
Section: Discussionmentioning
confidence: 58%
“…A total of 86% diabetic ulcers achieved complete wound closure. The recurrence rate was 4.2% in this meta‐analysis 52 . Diabetic leg, foot, and ankle wounds had wound healing rates of up to 70% after STSG in previously published case series 53,54 .…”
Section: Discussionmentioning
confidence: 49%
“…The recurrence rate was 4.2% in this meta-analysis. 52 Diabetic leg, foot, and ankle wounds had wound healing rates of up to 70% after STSG in previously published case series. 53,54 Rose et al, however, reported on a major limb amputation rate of 6% in diabetic wounds.…”
Section: Discussionmentioning
confidence: 91%
“…(V) Skin replacement therapy: compared with stem cell therapy, skin grafting could be proposed to treat noninfected diabetic wounds directly. A meta-analysis (19) indicated that, after a mean of 5.35 weeks, the rate of healed DF skin grafting was 85.5%, with recurrence, infection and regraft rates of 4.2%, 4.4% and 12.1%, respectively. However, considering the skin basis of patients with DF, the longer healing time limits the use of this method, spawning skin regeneration matrices for DF skin grafting, such as Integra, Nevelia, MatriDerm, Pelnac and Renoskin (20), but the high cost is a barrier to the application of these biological matrices.…”
Section: Original Articlementioning
confidence: 99%